Elevated temperature material properties of stainless steel reinforcing bar. (1st July 2016) - Gardner, L.; Bu, Y.; Francis, P.; Baddoo, N.R.; Cashell, K.A.; McCann, F.
Highlights: Review of use of stainless steel reinforcing bars. Isothermal and anisothermal testing of stainless steel reinforcing bars. Reduction factors proposed for key elevated temperature properties of stainless steel rebar. Room and elevated temperature stress-strain curves proposed for stainless steel rebar. Abstract: Corrosion of carbon steel reinforcing bar can lead to deterioration of concrete structures, especially in regions where road salt is heavily used or in areas close to sea water. Although stainless steel reinforcing bar costs more than carbon steel, its selective use for high risk elements is cost-effective when the whole life costs of the structure are taken into account. Considerations for specifying stainless steel reinforcing bars and a review of applications are presented herein. Attention is then given to the elevated temperature properties of stainless steel reinforcing bars, which are needed for structural fire design, but have been unexplored to date. A programme of isothermal and anisothermal tensile tests on four types of stainless steel reinforcing bar is described: 1.4307 (304L), 1.4311 (304LN), 1.4162 (LDX 2101®) and 1.4362 (2304). Bars of diameter 12 mm and 16 mm were studied, plain round and ribbed. Reduction factors were calculated for the key strength, stiffness and ductility properties and compared to equivalent factors for stainless steel plate and strip, as well as those for carbon steel reinforcement. The test results demonstrate that the reduction factors for 0.2% proof strength, strength at 2% strain and ultimate strength derived for stainless steel plate and strip can also be applied to stainless steel reinforcing bar. Revised reduction factors for ultimate strain and fracture strain at elevated temperatures have been proposed. The ability of two-stage Ramberg-Osgood expressions to capture accurately the stress-strain response of stainless steel reinforcement at both room temperature and elevated temperatures is also demonstrated.